Non-arthroplasty iliopsoas impingement in athletes: a narrative literature review. Issue 5 (September 2019) - Andronic, Octavian; Nakano, Naoki; Daivajna, Sachin; Board, Tim N; Khanduja, Vikas
Introduction: Iliopsoas impingement occurs secondary to a tight iliopsoas tendon that causes impingement during movement. This review presents current aspects regarding the diagnosis of iliopsoas impingement and also exposes the readers to the possible anatomic and clinical variations together with the available treatment options. Methods: We conducted a narrative literature review with regard to non-arthroplasty iliopsoas impingement. Results: Iliopsoas impingement is characterised by a distinct pattern of labral pathology, with anteriorly localised labral damage, that does not extend to the anterosuperior portion of the acetabulum. Anterior groin pain and intermittent catching, snapping or popping of the hip are common symptoms. Non-specific focal tenderness is often found over the iliopsoas tendon at the level of the anterior aspect of the joint. The 'C-sign' and Impingment test are usually positive. Dynamic ultrasonography is also useful for confirming the diagnosis. Initial management of painful iliopsoas impingement should be conservative. When patients continue to have pain, an ultrasound-guided injection can provide relief and predict the response to the surgical release. For patients who have recurrent pain after local injection of steroids, arthroscopic release has shown to achieve effective results. Conclusions: Although different treatment options for iliopsoas impingement are emerging, the current standard of therapy is conservative followed by an arthroscopic tenotomy if necessary. Young adult hip surgeons should always keep this differential in mind in a patient presenting with groin pain and mechanical symptoms.